Application of the Hill-Wheeler Formula in Statistical Models of Nuclear Fission: A Statistical–Mechanical Approach Based on Similarities with Semiconductor Physics - Hirokazu Maruyama (Entropy)
This study proposes a novel theoretical approach to understanding the statistical–mechanical similarities between nuclear fission phenomena and semiconductor physics. Using the Hill–Wheeler formula as a quantum mechanical distribution function and establishing its correspondence with the Fermi–Dirac distribution function, we analyzed nuclear fission processes for nine nuclides (232Th, 233U, 235U, 238U, 237Np, 239Pu, 240Pu, 242Pu, 241Am) using JENDL-5.0 data.